A Comparative Study of Performance Versions of Haydn’s “Sonata in G Major” (Hob. XVI/6) - Qun, Wei (Journal of Social Science and Humanities, 2025)
Haydn, one of the most influential composers of the Classical period, established the norms for the piano sonata genre and provided important creative paradigms for later composers. This paper takes his early piano sonata, the “Sonata in G Major” (Hob. XVI/6), as its subject. It selects recorded versions by three internationally renowned pianists and utilizes music performance research visualization software to generate spectrograms, waveform diagrams, and tempo-dynamic curves. Through this, it conducts a comparative analysis of the differences in key elements such as tempo, dynamics, and timbre across the performance versions. By comparing these versions, the study reveals the impact of different performance styles on the interpretation of the work, aiming to provide theoretical support and practical guidance for the academic research, performance practice, and teaching of Haydn’s piano sonatas.